Revelation and authority Sinai in Jewish scripture and tradition - Sommer, Benjamin D. 1964- (New Haven and London Yale University Press, 2015)
Participatory theories of revelation -- Artifact or Scripture? -- Revelation at Sinai, maximalist and minimalist approaches -- Command and law in the participatory theology of revelation -- Scripture as tradition, and tradition as Scripture -- Revelation event, process, and eternity -- A modern Jewish approach to Scripture -- Innovation, continuity, and covenant.
Winner of the 2016 Goldstein-Goren Award for the best book in Jewish Thought At once a study of biblical theology and modern Jewish thought, this volume describes a "participatory theory of revelation" as it addresses the ways biblical authors and contemporary theologians alike understand the process of revelation and hence the authority of the law. Benjamin Sommer maintains that the Pentateuch's authors intend not only to convey God's will but to express Israel's interpretation of and response to that divine will. Thus Sommer's close readings of biblical texts bolster liberal theologies of modern Judaism, especially those of Abraham Joshua Heschel and Franz Rosenzweig. This bold view of revelation puts a premium on human agency and attests to the grandeur of a God who accomplishes a providential task through the free will of the human subjects under divine authority. Yet, even though the Pentateuch's authors hold diverse views of revelation, all of them regard the binding authority of the law as sacrosanct. Sommer's book demonstrates why a law-observant religious Jew can be open to discoveries about the Bible that seem nontraditional or even antireligious
Includes bibliographical references and index
English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Rosenzweig, Franz -- 1886-1929 -- Influence; Heschel, Abraham Joshua -- 1907-1972 -- Influence; Heschel, Abraham Joshua; Rosenzweig, Franz; Bible -- Criticism, interpretation, etc; Bible; Revelation on Sinai; Rabbinical literature -- History and criticism; RELIGION ; Judaism ; General; RELIGION ; Judaism ; History; Influence (Literary, artistic, etc.); Rabbinical literature; Religion; Philosophy & Religion; Judaism; Criticism, interpretation, etc; Electronic books